Role of Mineral Mixture Supplementation in Enhancing Productivity and Profitability of Peri-urban Dairy farming - Sahoo, B. (Indian Journal of Animal Nutrition, 2021)
A study of 3 months duration was conducted in coastal belt of Odisha to assess the effect of supplemental mineral mixture on productive performance of lactating crossbred cows. Twenty crossbred cows were divided into two groups (T1 and T2) consisting of ten animals each. Animals in group T1(control) were fed on homemade concentrate mixture in fodder based diet consisting of concentrate and roughage (40:60), whereas the animals in group T2 were additionally supplemented with mineral mixture at 2% of concentrate mixture.Average daily dry matter intake (DMI), milk yield, milk composition were recorded at fortnight intervals during the trial. A digestibility trial of six days duration was conducted at the end of experimental feeding. DMI wasnot influenced by mineral mixture supplementation. Apparent digestibility of crude protein and ether extract were higher (P